1992
DOI: 10.1111/j.1365-2958.1992.tb02211.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of two variable proteins (PilE and PilC) required for pilus‐mediated adherence of Neisseria gonorrhoeae to human epithelial cells

Abstract: Pili confer the initial ability of Neisseria gonorrhoeae to bind to epithelial cells. Pilin (PilE), the major pilus subunit, and a minor protein termed PilC, reportedly essential for pilus biogenesis, undergo intra-strain phase and structural variation. We demonstrate here that at least two different adherence properties are associated with the gonococcal pili: one is specific for erythrocytes, which is virtually unaffected by PilE variation, and another is specific for epithelial cells, and is modulated in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
217
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(225 citation statements)
references
References 47 publications
8
217
0
Order By: Relevance
“…We found that four pili variants containing different PilE sequences (38) bound C4BP with similar apparent affinities (not shown). PilC is a 110-kDa pilus biogenesis protein that seems to be involved in the interaction between pili and MCP, because it was possible to select or genetically construct adherence negative mutants that expressed pili without detectable amounts of PilC (39,40). The results of an overlay assay suggested that C4BP interacts with the PilC subunit of pili.…”
Section: Discussionmentioning
confidence: 99%
“…We found that four pili variants containing different PilE sequences (38) bound C4BP with similar apparent affinities (not shown). PilC is a 110-kDa pilus biogenesis protein that seems to be involved in the interaction between pili and MCP, because it was possible to select or genetically construct adherence negative mutants that expressed pili without detectable amounts of PilC (39,40). The results of an overlay assay suggested that C4BP interacts with the PilC subunit of pili.…”
Section: Discussionmentioning
confidence: 99%
“…A 110-kD protein, pilC, present in small amounts in pill, is responsible for adherence to epithelial cells. The expression of this protein is subject to high frequency variation by a frame-shift mechanism due to a stretch of G residues early in the coding frame (10,11). The opacity proteins (opa) are also important adhesins.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the high frequency antigenic variation of GC LOS could be due to slipped strand mispairing during replication, causing premature termination of translation. This form of variation has been seen in the case of the pilC protein (10), a G.C pilus accessory protein imparting adhesiveness to epithelial cells (11). The glycosyl transferases that might be subject to this form of variation are IgtA, the GlcNAc transfer~tse; lgtD, the GalNAc transferase; and IgtC, the Gal Xransferase responsible for the addition of o~Gall-4f3Gal.…”
Section: Sultlnlarymentioning
confidence: 99%
“…However, several studies have suggested a role for the pilin subunit PilE in receptor recognition. These include numerous findings showing that different antigenic variant forms of PilE influence epithelial cell adherence and tissue tropism (12,(14)(15)(16). However, the structural and functional attributes of PilE accounting for these observations remain unknown.…”
mentioning
confidence: 99%
“…The conclusion that PilC is a neisserial Tfp-associated adhesin is based primarily on the findings that (i) purified recombinant PilC imparts human epithelial cell binding activity on latex beads to which it has been coupled and blocks binding of piliated organisms to human epithelial cells (7) and (ii) piliated mutants lacking PilC fail to adhere (12,13). However, several studies have suggested a role for the pilin subunit PilE in receptor recognition.…”
mentioning
confidence: 99%